Prevalence of asthma-like symptoms and assessment of lung function in schoolchildren born with low birth weight - Zainal, Nik; Rahardja, Andy; Faris Irfan, Che Yusoff; Nasir, Ariffin; Wan Pauzi, Wan Ibrahim; Mohamad Ikram, I.; Van Rostenberghe, Hans (Singapore Medical Association, 2016)
This study aimed to determine the prevalence of asthma-like symptoms among schoolchildren with low birth weight (LBW), and to compare the lung function of these children with that of children with normal birth weight. METHODS This was a comparative cross-sectional study. We recruited children aged 8-11 years from eight primary schools in Kota Bharu, Kelantan, Malaysia. The children were divided into two groups: those with LBW (< 2,500 g) and those with normal birth weight (≥ 2,500 g). Parents of the enrolled children were asked to complete a translated version of the International Study of Asthma and Allergies in Childhood questionnaire. Lung function tests, done using a MicroLoop Spirometer, were performed for the children in both groups by a single investigator who was blinded to the children’s birth weight. RESULTS The prevalence of ‘ever wheezed’ among the children with LBW was 12.9%. This value was significantly higher than that of the children with normal birth weight (7.8%). Forced vital capacity (FVC), forced expiratory volume in one second, and forced expiratory flow when 50% and 75% of the FVC had been exhaled were significantly lower among the children with LBW as compared to the children with normal birth weight. CONCLUSION LBW is associated with an increased prevalence of asthma-like symptoms and impaired lung function indices later in life. Children born with LBW may need additional follow-up so that future respiratory problems can be detected early